A STUDY OF EARLY ADOPTERS OF PERSONAL COMPUTERS AMONG MANAGERIAL PERSONNEL IN SINGAPORE : PERSONAL CHARACTERISTICS AND PERCEIVED PRODUCT ATTRIBUTES AS PREDICTORS OF INNOVATIVENESS - GEOFFREY DA SILVA (2019)
Master's